Letter - Butler, E.J.
1941-02-26 038-0034-002 BASQUE CHILDREN FUND TRADES COUNCIL COMM 5 ALTON TERR NORTH HILL PLYMOUTH Mr Tewson Transport House Smith Square London SW1 Feb. 26th 1941 Dear Mr Tewson Some time ago I appealed to the TUC through you for help towards the maintenance of the 12 children in Plymouth On your Reply stating that all the help you could afford was sent to the National Basque Childrens Fund, I wrote to this committee, the reply I received stated they had only received 10 from the T.U.C. according to their records. After further correspondence, I have been asked by the Basque Children's Committee to write to you and find what financial assistance has been given by the T.U.C. Hoping you will furnish me with this information. And thanking you in anticipation Yours sincerely E.J. Butler. Hon. Sec. 292/946/38/34(II)